Stainless steel material and its manufacturing method, and workpiece and its manufacturing method
A stainless steel material with controlled composition and heat-treatment forms a black oxide film that resists peeling and maintains corrosion resistance during processing.
Patent Information
- Application Number
- JP2023113235
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Stainless steel materials with black oxide films tend to peel off during processing, leading to a loss of black tone and reduced corrosion resistance.
A stainless steel material with controlled composition and oxide film characteristics, including specific element percentages and heat-treatment conditions, forms a black oxide film that is resistant to peeling during processing.
The solution provides a stainless steel material with a black oxide film that remains intact during processing and maintains good corrosion resistance.
Smart Images

Figure 2025010922000001 
Figure 2025010922000002 
Figure 2025010922000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a stainless steel material and a manufacturing method thereof, and a processed product and a manufacturing method thereof. [Background technology]
[0002] Stainless steel is a material with excellent corrosion resistance, and taking advantage of its shiny silver-white surface, it is used in various products such as interior and exterior building materials, exhaust system parts, etc. In order to enhance the design of stainless steel, it is often given a color tone, typically black, using methods such as chemical coloring, painting, and oxidation treatment.
[0003] For example, the method of forming an oxide film on the surface of stainless steel (material) by oxidation treatment methods such as those described in Patent Documents 1 and 2 allows for continuous treatment using continuous annealing equipment, which is a general-purpose manufacturing process for stainless steel, and has higher productivity than other treatments such as chemical coloring. The oxide film formed by this oxidation treatment method has good corrosion resistance because a layer mainly made of protective Cr oxide is formed. Patent Documents 3 to 6 also propose techniques for forming a black oxide film with good corrosion resistance by controlling the composition of the stainless steel material and the conditions during oxidation treatment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-178392 A [Patent Document 2] JP 2018-135591 A [Patent Document 3] JP 2022-103735 A [Patent Document 4] JP 2022-103732 A [Patent Document 5] Japanese Patent Application Publication No. 11-061376 [Patent Document 6] Japanese Patent Application Publication No. 10-330904 Summary of the Invention [Problem to be solved by the invention]
[0005] Stainless steel materials having a black oxide film are generally subjected to various processes such as bending and pressing in order to manufacture various products. In this case, conventional stainless steel materials have a problem that the black oxide film is easily peeled off due to galling between the black oxide film and processing jigs such as dies and bending jigs. Here, "galling" refers to the phenomenon in which the black oxide film peels off due to friction with the processing jig. When the black oxide film peels off, it becomes difficult to maintain the black color tone, and the corrosion resistance is also easily reduced.
[0006] The present invention has been made to solve the above-mentioned problems, and has an object to provide a stainless steel material having a black oxide coating that is difficult to peel off during processing and has good corrosion resistance, a manufacturing method thereof, and a processed product and a manufacturing method thereof. [Means for solving the problem]
[0007] The present inventors conducted extensive research into a stainless steel material having a base part and an oxide film formed on the base part, and as a result, found that the above-mentioned problems can be solved by controlling the thickness, carrier density, and refractive index of the oxide film as well as the composition of the base part. The present inventors also found that a stainless steel material having such characteristics can be obtained by heat treating a rolled material having a predetermined composition under predetermined conditions. The present invention was completed against this background.
[0008] That is, the present invention provides a stainless steel material having a material part and an oxide film formed on the material part, the material portion has a composition, on a mass basis, of C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities; The oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0 × 10 20 pieces / cm 3 The following is a stainless steel material having a refractive index of 1.5 or less.
[0009] The present invention also relates to a rolled material having a composition, on a mass basis, of C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities, wherein the O2 concentration is 2 to 20% by volume, the water vapor concentration is 20% by volume or less, and the following formula (1): 2 × O2 concentration + water vapor concentration (1) This method involves heating the stainless steel material in an atmosphere in which the value represented by the formula (I) is 15 to 30 in a temperature range of 500 to 800°C at a heating rate of 10 to 20°C / sec, and then conducting heat treatment at a temperature of 800°C or higher for 1 minute or more.
[0010] The present invention also relates to a processed product of the stainless steel material, in which an exposed area ratio of the material portion is 10% or less. Furthermore, the present invention relates to a method for manufacturing the stainless steel material using a kinetic viscosity of 65 mm 2 The present invention relates to a method for manufacturing a processed product, the method including processing a processed product using a processing oil having a viscosity of 10000 / s or more. Effect of the Invention
[0011] According to the present invention, it is possible to provide a stainless steel material having a black oxide film that is difficult to peel off during processing and also has good corrosion resistance, a manufacturing method thereof, and a processed product and a manufacturing method thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0013] <Stainless steel material> A stainless steel material according to an embodiment of the present invention has a material part and an oxide film formed on the material part. Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape.
[0014] The material portion has a composition containing C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities. In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level).
[0015] If necessary, the material part may further contain at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less. Each component will be described in detail below.
[0016] (C: 0.100% or less) C is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. However, if the C content is too high, the workability and intergranular corrosion resistance of the stainless steel material will decrease. Therefore, the upper limit of the C content is 0.100%, preferably 0.080%, and more preferably 0.060%. On the other hand, the lower limit of the C content is not particularly limited, but excessively reducing the C content leads to an increase in refining costs. Therefore, the lower limit of the C content is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%.
[0017] (Si:1.00% or less) Silicon is an element that improves the oxidation resistance of stainless steel materials. However, if the content of silicon is too high, the workability and the toughness of the welded joint are reduced. Therefore, the upper limit of the content of silicon is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the content of silicon is not particularly limited, but is preferably 0.005%, more preferably 0.01%, and even more preferably 0.015% from the viewpoint of obtaining the effect of silicon.
[0018] (Mn: 0.05 to 1.00%) Mn is an element that is effective in ensuring the color tone of the oxide film (blackened film after heat treatment). In particular, Mn gives a black color tone by forming a complex oxide with Cr. However, if the Mn content is too high, MnS, which is the starting point of corrosion, is easily generated and the ferrite phase is destabilized. Therefore, the upper limit of the Mn content is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, if the Mn content is too low, the above effects may not be sufficiently obtained. Therefore, the lower limit of the Mn content is 0.05%, preferably 0.055%, and more preferably 0.06%.
[0019] (Ni: 1.00% or less) Ni is an element effective for improving the corrosion resistance and weld toughness of stainless steel materials. However, if the Ni content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Ni content is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the Ni content is not particularly limited, but is preferably 0.005%, and more preferably 0.01%, from the viewpoint of obtaining the above-mentioned effects.
[0020] (P:0.100% or less) P is an element that affects the properties of stainless steel materials, such as weldability and workability. If the P content is too high, the above properties may be degraded. Therefore, the upper limit of the P content is 0.100%, preferably 0.080%, and more preferably 0.060%. On the other hand, the lower limit of the P content is not particularly limited, but an excessively low P content leads to an increase in refining costs. Therefore, the lower limit of the P content is preferably 0.001%, and more preferably 0.005%.
[0021] (S:0.100% or less) S is an element that generates MnS, which is a corrosion starting point, and affects the properties of stainless steel materials, such as the toughness of welded parts. If the S content is too high, the above properties may be deteriorated. Therefore, the upper limit of the S content is 0.100%, preferably 0.080%, and more preferably 0.060%. On the other hand, the lower limit of the S content is not particularly limited, but excessively reducing the S content leads to an increase in refining costs. Therefore, the lower limit of the S content is preferably 0.0001%, and more preferably 0.0002%.
[0022] (Cr:16.00~25.00%) Cr is an element that is effective in improving the corrosion resistance of stainless steel materials and forming a uniform oxide film. Cr is also an element that is effective in ensuring the color tone of the oxide film (blackened film after heat treatment). However, if the Cr content is too high, the manufacturing cost increases. Therefore, the upper limit of the Cr content is 25.00%, preferably 24.00%, and more preferably 23.00%. On the other hand, if the Cr content is too low, the above effects cannot be sufficiently obtained. Therefore, the lower limit of the Cr content is 16.00%, preferably 16.50%, and more preferably 17.00%.
[0023] (N:0.100% or less) N is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. However, if the N content is too high, the intergranular corrosion resistance and workability of the stainless steel material will decrease. In addition, if the N content is high, TiN will easily precipitate, the amount of solid-solubilized Ti in the steel will decrease, and the formation of a blackened film after heat treatment will be inhibited. In addition, the formed nitrides are likely to become the starting point of corrosion, reducing the corrosion resistance. Therefore, the upper limit of the N content is 0.100%, preferably 0.095%, and more preferably 0.090%. On the other hand, the lower limit of the N content is not particularly limited, but an excessively low N content will lead to an increase in refining costs. Therefore, the lower limit of the N content is preferably 0.001%, and more preferably 0.003%.
[0024] (Ti: 0.08~0.50%) Ti is an element that affects the intergranular corrosion resistance (sensitization suppression effect) of stainless steel materials. In addition, Ti is also an element that is effective in ensuring the color tone of the oxide film (blackened film after heat treatment). In particular, Ti gives a black color tone by forming a composite oxide with Cr, and can also suppress peeling of the oxide film by forming Ti oxide (TiO2) on the surface. However, if the Ti content is too high, the workability and surface quality of the stainless steel material are reduced. Therefore, the upper limit of the Ti content is 0.50%, preferably 0.45%, and more preferably 0.40%. Also, if the Ti content is too low, the above-mentioned effects cannot be sufficiently obtained. Therefore, the lower limit of the Ti content is 0.08%, preferably 0.085%, and more preferably 0.09%.
[0025] (Cu:1.00% or less) Cu is an element effective for improving the corrosion resistance of stainless steel materials. However, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Cu content is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.005%, and more preferably 0.01%.
[0026] (Mo: 2.00% or less) Mo is an element effective for improving the corrosion resistance and oxidation resistance of stainless steel materials. However, if the Mo content is too high, it leads to a decrease in the workability of the stainless steel material and an increase in the manufacturing cost. Therefore, the upper limit of the Mo content is 2.00%, preferably 1.95%, and more preferably 1.90%. On the other hand, the lower limit of the Mo content is not particularly limited, but is preferably 0.001%, and more preferably 0.01%.
[0027] (Nb:0.50% or less) Nb is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect). However, if the Nb content is too high, the workability of the stainless steel material decreases. Therefore, the upper limit of the Nb content is 0.50%, preferably 0.45%, and more preferably 0.40%. On the other hand, the lower limit of the Nb content is not particularly limited, but is preferably 0.005%, and more preferably 0.01%.
[0028] (Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less) Al, Zr, Co, V and W are elements effective for improving the oxidation resistance of stainless steel materials. However, if the content of Al, Zr, Co, V and W is too high, the workability and toughness of the stainless steel material will decrease, and the manufacturing cost will increase. Therefore, the upper limit of the content of Al, Zr, Co, V and W is 1.00%, preferably 0.95%, and more preferably 0.90%. On the other hand, the lower limit of the content of Al, Zr, Co, V and W is not particularly limited, but is preferably 0.0001%, more preferably 0.001%, and even more preferably 0.01%.
[0029] (REM: 0.100% or less, Ca: 0.100% or less) REM and Ca are elements effective for improving the oxidation resistance of stainless steel materials. However, if the REM and Ca contents are too high, it leads to an increase in the manufacturing cost of stainless steel materials. Therefore, the upper limit of the REM and Ca contents is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the REM and Ca contents is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%. In addition, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and refers to rare earth metals. Specifically, La, Ce, Nd, etc. can be mentioned, and one of these can be contained alone or two or more can be combined. When two or more rare earth elements are contained, the content of the REM refers to the total content of these rare earth elements.
[0030] (Sn:0.100% or less) Sn is an element effective for improving the corrosion resistance of stainless steel materials. However, if the Sn content is too high, Sn segregates and manufacturability decreases. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the Sn content is not particularly limited, but is preferably 0.001%, and more preferably 0.002%.
[0031] (B:0.0100% or less) B is an element effective for improving the secondary workability of stainless steel materials. However, if the B content is too high, the fatigue strength of the stainless steel material decreases. Therefore, the upper limit of the B content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the B content is not particularly limited, but is preferably 0.0001%, and more preferably 0.0003%.
[0032] The metal structure of the material portion is ferritic. In this specification, "ferritic" means that the metal structure at room temperature is mainly in the ferritic phase.
[0033] Next, the oxide film formed on the material portion will be described. The oxide film has the function of imparting corrosion resistance and a black color tone to the stainless steel material. The oxide film has a Cr2O3 inner layer and may have a Mn-Cr oxide layer on the outermost surface.
[0034] The Cr2O3 inner layer is the layer on the material side of the oxide film, and has the function of ensuring the barrier properties of the oxide film (its ability to protect the material). The Mn-Cr oxide layer is the surface layer of the oxide film. It is a layer composed of a composite oxide of Mn and Cr (Mn-Cr spinel oxide) and has the function of imparting a black color tone to the oxide film.
[0035] The oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0 × 10 20 pieces / cm 3 The refractive index of the oxide film is 1.5 or less. * a * b * Lightness index L in color system * is 50.0 or less, Chromathetics Index a * and b * It is preferable that the difference is within ±5.00. The reasons for these limitations will be explained.
[0036] (Thickness: 300~1000nm) The thickness of the oxide film (the entire oxide film including the Cr2O3 inner layer and the Mn-Cr oxide layer) affects the color tone. From the viewpoint of imparting a desired black color tone, the lower limit of the oxide film thickness is 300 nm, preferably 310 nm, and more preferably 320 nm. On the other hand, if the oxide film is too thick, it is more likely to crack or peel off during processing of the stainless steel material. Therefore, the upper limit of the oxide film thickness is 1000 nm, preferably 950 nm, and more preferably 900 nm. In this specification, the thickness of the oxide film is defined as the depth from the surface to the position where O (oxygen) is 1 / 4 of the maximum value in the component concentration profile in the depth direction obtained by glow discharge optical emission spectroscopy (GD-OES). The concentration of the element can be determined by glow discharge optical emission spectroscopy (GD-OES).
[0037] (Carrier density: 2.0×10 20 pieces / cm 3 below) Metal corrosion progresses as a result of the pairing of metal dissolution (anodic reaction) and oxygen reduction (cathodic reaction) around the metal dissolution area. This is because electrical neutrality is maintained by consuming electrons generated in the anodic reaction in the cathodic reaction. Therefore, if the cathodic reaction in stainless steel materials can be suppressed, the anodic reaction (metal dissolution) can also be suppressed. The cathodic reaction occurs in an environment where water is present, when electrons generated in the anodic reaction move inside the metal and react with oxygen dissolved in the water on the surface. Therefore, the cathodic reaction can be suppressed by covering the surface of the metal with an insulating material that makes it difficult for electrons to move. However, an oxide film mainly composed of Cr2O3 does not have sufficient insulation because structural defects (e.g., oxygen vacancies or metals with a different valence from Cr) act as carriers that carry the electrons, and the cathodic reaction cannot be sufficiently suppressed. Therefore, in order to sufficiently suppress the cathodic reaction in stainless steel materials, it is important to control the carrier density of the oxide film.
[0038] For the above reasons, the upper limit of the carrier density of the oxide film is 2.0×10 20 pieces / cm 3 , preferably 1.0 x 10 20 pieces / cm 3 In addition, by setting the upper limit of the carrier density of the oxide film as described above, corrosion is less likely to occur even if the material is partially exposed during processing. On the other hand, the lower limit of the carrier density of the oxide film is not particularly limited because the smaller the lower limit, the greater the effect of suppressing the cathodic reaction. Generally, however, it is set to 1.0×10 14 pieces / cm 3 , preferably 1.0 x 10 15 pieces / cm 3 It is. In this specification, the carrier density of the oxide film can be measured by electrochemical impedance measurement.
[0039] (Refractive index: 1.5 or less) The refractive index of the oxide film is an index representing the porosity (number of defects) of the outermost layer of the oxide film. When the porosity of the outermost layer of the oxide film is high, the outermost layer of the oxide film can hold processing oil during processing of the stainless steel material, so that the oxide film can be prevented from galling with the processing tool, and the oxide film is less likely to peel off. In order to obtain such an effect, it is important to set the refractive index of the oxide film to 1.5 or less. If the refractive index of the oxide film is 1.5 or less, it can be said that the porosity of the outermost layer of the oxide film is sufficiently high. From the viewpoint of stably securing the above effect, the refractive index of the oxide film is preferably 1.4 or less, and more preferably 1.3 or less. The lower limit of the refractive index of the oxide film is not particularly limited, but is typically 0.5. In this specification, the refractive index of the oxide film can be measured by an ellipsometry method.
[0040] (Lightness index L * : 50.0 or less, Chromathetics index a * and b * : within ±5.00) The oxide film is L * a * b * Lightness index L in color system * is 50.0 or less, Chromathetics Index a * and b * is within ±5.00. * , Chromathetics Index a * and b * Within the above range, it can be said that a desired black tone is obtained. Here, in this specification, "brightness index L * " and "Chromathetics Index a * and b * " can be measured in accordance with JIS Z8722:2009.
[0041] The stainless steel material according to the embodiment of the present invention has a black oxide film that is difficult to peel off during processing and has good corrosion resistance, so it can be used in various applications where these properties are required. Specifically, the stainless steel material according to the embodiment of the present invention is suitable for use in exhaust system parts such as mufflers, exterior and interior building panels, etc.
[0042] <Method of manufacturing stainless steel materials> The method for producing a stainless steel material according to the embodiment of the present invention is not particularly limited as long as it is a method capable of producing a stainless steel material having the above-mentioned characteristics. The stainless steel material according to the embodiment of the present invention can be manufactured by using a rolled material having the above-mentioned composition as a raw material and by heat treating this rolled material under predetermined conditions.
[0043] The rolled material is not particularly limited, and may be a hot-rolled material, a cold-rolled material, or the like. The rolled material may be manufactured according to a method known in the art. For example, the cold-rolled material may be manufactured by melting stainless steel having a predetermined composition, hot rolling, annealing, pickling, and then cold rolling. The rolled material may be subjected to various treatments (annealing, pickling, polishing, etc.) after rolling.
[0044] The heat treatment of the rolled material is performed in an atmosphere in which the O2 concentration is 2 to 20 volume %, the water vapor concentration is 20 volume % or less, and the value represented by the following formula (1) is 15 to 30, by heating in the temperature range of 500 to 800°C at a heating rate of 10 to 20°C / sec, and maintaining the temperature at 800°C or higher for 1 minute or more. 2 × O2 concentration + water vapor concentration (1) By carrying out heat treatment under these conditions, it is possible to form a black oxide film that is difficult to peel off during processing, and also to improve the corrosion resistance of the stainless steel material. In particular, by setting the heating rate in the temperature range of 500 to 800°C at 10 to 20°C / sec, the oxidation of Mn in the outermost layer of the oxide film is promoted, and the porosity of the outermost layer of the oxide film can be increased.
[0045] If the O2 concentration exceeds 20% by volume, the Cr diffusion in the material slows down and the Cr concentration in the surface layer of the material decreases, making it difficult to form an oxide film with the desired properties. On the other hand, if the O2 concentration is less than 2% by volume, it becomes difficult to form an oxide film with a predetermined thickness. From the viewpoint of stably forming an oxide film with the desired properties and thickness, the O2 concentration is preferably 2 to 18% by volume, and more preferably 2 to 15% by volume. If the water vapor concentration exceeds 20% by volume, the Cr concentration at the interface between the material part and the oxide film becomes high, and the desired corrosion resistance cannot be obtained. From the viewpoint of stably reducing the Cr concentration at the interface between the material part and the oxide film, the water vapor concentration is preferably 18% by volume or less, and more preferably 16% by volume or less.
[0046] If the value represented by formula (1) is outside the range of 15 to 30, the oxidation rate cannot be appropriately controlled, and it becomes difficult to form an oxide film having the desired properties and thickness. From the viewpoint of stably controlling the oxidation rate, the value represented by formula (1) is preferably 16 to 28, and more preferably 18 to 25.
[0047] If the heating rate in the temperature range of 500 to 800°C exceeds 20°C / sec, it becomes difficult to efficiently oxidize Mn in the outermost layer of the oxide film. If the heating rate in this temperature range is less than 10°C / sec, the carrier density increases and the corrosion resistance decreases. From the viewpoint of stably promoting the oxidation of Mn in the outermost layer of the oxide film, the heating rate is preferably 12 to 19°C / sec, more preferably 13 to 18°C / sec.
[0048] If the heat treatment temperature is less than 800° C. and the heat treatment time is less than 1 minute, the oxide film will not grow sufficiently and an oxide film of the desired thickness will not be formed. The heat treatment temperature is preferably 900 to 1200°C, and more preferably 950 to 1180°C, from the viewpoint of stably forming an oxide film having the desired characteristics and thickness. Moreover, from the viewpoint of stably forming an oxide film having the desired characteristics and thickness, the heat treatment time is preferably 2 to 500 minutes, and more preferably 2 to 100 minutes.
[0049] <Processed products> The processed product according to the embodiment of the present invention is a processed product made of the above-mentioned stainless steel material. In this specification, the processed product of stainless steel material means a product obtained by processing stainless steel material by various known methods. The processing method is not particularly limited, but examples thereof include pressing, bending, polishing, roll forming, etc.
[0050] The processed product according to the embodiment of the present invention may have a portion where the material part is exposed in a part of the processed part. Even if the processed product according to the embodiment of the present invention has a portion where the material part is exposed, the portion is unlikely to corrode, and therefore the corrosion resistance of the processed product can be improved. The exposed area ratio of the material part is 10% or less. By controlling the exposed area ratio of the material part within this range, corrosion of the material part can be stably suppressed. In this specification, the "exposed area ratio of the material part" means the ratio of the area of the material part exposed in the processed part that is in contact with the processing tool. The exposed area ratio of the material part can be obtained by measuring the color tone to identify the exposed part of the material part and calculating the area ratio.
[0051] The processed product according to the embodiment of the present invention has a black oxide film that is difficult to peel off during processing, and has good corrosion resistance even if the material part is partially exposed during processing. Therefore, the processed product can be used in applications where such characteristics are required. Specifically, the processed product according to the embodiment of the present invention is suitable for use as exhaust system parts such as mufflers, exterior and interior building material panels, etc.
[0052] <Manufacturing methods for processed products> The processed product according to the embodiment of the present invention is made of the above-mentioned stainless steel material having a kinetic viscosity of 65 mm 2 This includes machining using a processing oil for more than 1 / 2 second. By using a processing oil with such a kinetic viscosity, it becomes easier to retain the processing oil in the outermost layer of the oxide film when machining stainless steel material, thereby suppressing the galling between the oxide film and the machining jig and making the oxide film less likely to peel off. The processing oil is not particularly limited as long as it has the above-mentioned kinetic viscosity, and commercially available processing oils can be used.
[0053] The processing method is not particularly limited as described above. The processing conditions are also not particularly limited and may be appropriately adjusted depending on the processing method. EXAMPLES
[0054] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0055] Stainless steel having the composition shown in Table 1 (the balance being Fe and impurities) was melted and hot rolled to obtain a hot rolled sheet with a thickness of 3.0 mm, which was then annealed at 1050°C and pickled to obtain a hot rolled annealed sheet. Next, the hot rolled annealed sheet was cold rolled to obtain a cold rolled sheet with a thickness of 1.2 mm. Next, the cold rolled sheet was heat treated under the conditions shown in Table 2 to obtain a stainless steel sheet. In the heat treatment, the introduction ratio of O2 gas, N2 gas, and water vapor was adjusted in the atmosphere furnace to control the O2 concentration and water vapor concentration to the specified values. A test piece of 300 mm (rolling direction) x 100 mm (width direction) was cut out from the obtained stainless steel sheet.
[0056] [Table 1]
[0057] [Table 2]
[0058] The above test pieces were subjected to the following evaluations.
[0059] (Oxide film thickness) A 50 mm square measurement specimen was cut out from the test piece, and the surface was degreased with acetone. Next, analysis was performed using glow discharge optical emission spectroscopy (GD-OES) in accordance with JIS K0144:2018. In GD-OES, the thickness of the oxide film was defined as the depth from the surface to the position where O (oxygen) was 1 / 4 of the maximum value in the component concentration profile in the depth direction obtained. The concentration of elements was calculated from the component concentration profile in the depth direction obtained by GD-OES.
[0060] (Carrier density of oxide film) A 20mm x 15mm test specimen was cut out from the test piece, a conductor was spot welded to one end, and the rest of the test surface (10mm x 10mm) was covered with silicone resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, a 0.1 mol / L Na2SO4 aqueous solution was used as the test liquid, and electrochemical impedance measurements were performed at 30°C in an Ar deaerated atmosphere. The electrochemical impedance measurements were performed using an electrochemical measurement system HZ-7000 manufactured by Hokuto Denko Co., Ltd., and a sine wave was applied at a predetermined potential to measure the impedance change, and the capacitance C of the oxide film was measured. The measurement potential was -0.2 to 0.5V vs. SSE (SSE indicates a saturated KCl silver-silver chloride electrode type reference electrode), sine wave 1Hz to 100kHz, and amplitude 10mV. Based on the obtained C, a 1 / C plot called a Mott-Schottky plot was performed. 2 In the graph of the -V curve, the slope A of the graph from 0 to -0.4 V was derived by the least squares method. The slope A and the carrier density N q is expressed by the following formula, and the carrier density of the oxide film was derived from the slope A based on this formula.
[0061]
number
[0062] In the above formula, N q is the carrier density, A is the slope of the Mott-Schottky plot, and e is the elementary charge (1.62×10 -19C), ε is the relative dielectric constant of the oxide film (12), and ε0 is the dielectric constant of a vacuum (8.854×10 -12 F / m).
[0063] (Refractive index of oxide film) A 50 mm square measurement specimen was cut out from the test piece, and the surface was degreased with acetone. Next, an ellipsometry measurement device (UVISEL spectroscopic ellipsometer manufactured by Horiba, Ltd.) was used to measure the refractive index for light with a wavelength of 600 nm under the conditions of an incident angle of 70°, a measurement wavelength range of 0.6 to 5.0 eV, and an elliptical spot diameter of 1 mm x 3 mm.
[0064] (color tone) The color tone of any five points on the test piece is measured using a spectrophotometer with a measurement diameter of 3 mm in accordance with JIS Z8722:2009, and the average value is calculated as CIELAB(L) in accordance with JIS Z8781-4:2013. * a * b * The lightness index L * , Chromathetics Index a * , b * As shown in.
[0065] The conditions for measuring the above color tone were as follows: Equipment: Konica Minolta CM-700d spectrophotometer Light source: Pulsed xenon lamp Photodetector: Dual 36-element silicon photodiode array Target mask: φ3mm Measurement: 10° field of view Auxiliary Illuminant: D65 daylight, color temperature 6504K Specular reflection processing mode: SCI
[0066] (processability) A processing test piece with a diameter of 80 mm was cut out from the test piece, and the surface was degreased with acetone. Next, processing oil having a kinetic viscosity shown in Table 3 was applied to the processing test piece, and deep drawing was performed. The deep drawing was performed with a punch diameter of 40 mm, a die diameter of 44 mm, a blank holding pressure of 10 kN, and a drawing speed of 20 mm / min. After processing, the color tone of the side of the processed product (the part in contact with the punch and die) was measured to identify the part where the material part was exposed, and the exposed area ratio of the material part was obtained by calculating the area ratio.
[0067] (Corrosion resistance: CCT test) A test piece measuring 50 mm wide and 100 mm long was cut out from the test piece. The test piece was then used to evaluate the corrosion resistance by a combined cycle test (CCT) test. The CCT test was performed as follows. First, three sides of the test specimen (except one side in the width direction) were covered with resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, two polyethylene tubes of 20 mmφ×10 mm were bonded onto a 70 mm×150 mm Bakelite plate, and the side of the test specimen that was not covered with resin and the opposite side were placed on top of the tubes and bonded. Next, the sample obtained in this way was placed in a CCT device so that the surface of the test specimen was at 75° to the horizontal plane and the side of the test specimen that was not covered with resin was at the bottom, and 10 cycles were performed, with 5% salt spray (35°C, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours) as one cycle. After that, the sample was washed with water and dried, and the rust area ratio on the surface of the test specimen was evaluated (in accordance with JIS Z2371:2015). In this evaluation, a rating number (RN) of 8.0 or higher indicates good corrosion resistance. The above results are shown in Table 3.
[0068] [Table 3]
[0069] As shown in Table 3, the stainless steel plates of Examples 1 to 5 had the composition of the base material, the thickness of the oxide film, the carrier density, and the refractive index within the specified ranges, so that even when processed, there was little exposure of the base material (i.e., the oxide film was less likely to peel off), and the corrosion resistance and black design were good.
[0070] In contrast, the stainless steel sheet of Comparative Example 1 had an inappropriate atmosphere during heat treatment (the water vapor concentration and the value of formula (1) were too high), so the carrier density was large and the corrosion resistance was reduced. The stainless steel sheet of Comparative Example 2 had an inappropriate atmosphere during heat treatment (the value of formula (1) was too high), and therefore the carrier density was large and the corrosion resistance was reduced. The stainless steel sheet of Comparative Example 3 was heat-treated in an inappropriate atmosphere (the O2 concentration and the value of formula (1) were too low), so the thickness of the oxide film was small and the black design could not be secured. In the stainless steel plate of Comparative Example 4, the temperature rise rate during heat treatment was too fast, so that the refractive index increased and the base material was more exposed during processing (that is, the oxide film was more likely to peel off). In the stainless steel material of Comparative Example 5, the heating rate during the heat treatment was too slow, so that the carrier density increased and the corrosion resistance decreased. The stainless steel material of Comparative Example 6 had an excessively low Cr content, and therefore the carrier density was high and the corrosion resistance was reduced. The stainless steel material of Comparative Example 7 had an excessively low Mn content, which resulted in an increased refractive index and increased exposure of the base material during processing (that is, the oxide film was easily peeled off). In the stainless steel material of Comparative Example 8, the kinetic viscosity of the processing oil used during processing was too low, so that the material was exposed to a large extent during processing (i.e., the oxide film was easily peeled off), and the corrosion resistance was also reduced.
[0071] As can be seen from the above results, according to the present invention, it is possible to provide a stainless steel material having a black oxide coating that is difficult to peel off during processing and also has good corrosion resistance, a manufacturing method thereof, and a processed product and a manufacturing method thereof.
Claims
1. A stainless steel material having a material portion and an oxide film formed on the material portion, the material portion has a composition including, by mass, C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities; The oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0×10 20 pieces / cm 3 Hereinafter, a stainless steel material having a refractive index of 1.5 or less.
2. The stainless steel material according to claim 1, wherein the material portion further contains, by mass, at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
3. The oxide film is L * a * b * Lightness index L in color system * is 50.0 or less, Chromathetics Index a * and b * The stainless steel material according to claim 1 or 2, wherein the value is within ±5.
00.
4. A rolled material having a composition containing, on a mass basis, C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities, is 2 The concentration is 2 to 20% by volume, the water vapor concentration is 20% by volume or less, and the following formula (1): 2 x O 2 Concentration + water vapor concentration ... (1) The method for producing a stainless steel material comprises heating the material to a temperature range of 500 to 800°C at a heating rate of 10 to 20°C / sec in an atmosphere in which the value represented by the formula (I) is 15 to 30, and then performing heat treatment at a temperature of 800°C or higher for 1 minute or more.
5. The method for producing a stainless steel material according to claim 4, wherein the rolled material further contains, by mass, at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
6. A processed product of the stainless steel material according to claim 1 or 2, A processed product in which the exposed area ratio of the material portion is 10% or less.
7. The stainless steel material according to claim 1 or 2 is subjected to a kinetic viscosity of 65 mm 2 A method for producing a processed product, comprising processing the product using a processing oil having a viscosity of 100 / s or more.
Citation Information
Patent Citations
Production of black-colored ferritic stainless steel
JP1998330904A
Black stainless steel plate and its production
JP1999061376A
Black ferritic stainless steel sheet
JP2018135591A
Black stainless steel sheet and method for manufacturing the same
JP2019178392A
Ferritic stainless steel material
JP2022103732A